The Leading of Financial Investment Awareness among Generation Z in Indonesia - Pinudom, Tuangporn; Kunnapapdeelert, Siwaporn; Phalitnonkiat, Passarin; Charis Rorong, Aldrin; Farrell Febriansyah, Ezra (วารสารการวิจัยการบริหารการพัฒนา, 2024)
Currently, there is more awareness of financial education and literacy to Generation Z in several countries. As Generation Z is the large group of population and plays an important role in economic development. This generation faces financial challenges and technological advancement. Therefore, creating financial investment awareness is crucial for Generation Z. However, financial investment awareness of Generation Z is affected by several factors. This research emphasized the study of the influences of financial investment awareness among Generation Z in Indonesia as Indonesia’s population is dictated by Generation Z and the millennial generation. Generation Z makes up 27.94% of the total population. This generation can possibly affect the economic growth of Indonesia. The data were collected by surveying 259 respondents and analyzed by Structural Equation Modeling (SEM). The research result showed three critical variables influencing financial investment awareness of Generation Z: financial attitude, family monetary socialization, and saving behavior. All three components have positive impacts on investment awareness